OPTIMASI PRODUKSI RESERVOIR GAS KERING X DENGAN PENURUNAN TEKANAN INLET KOMPRESOR UNTUK PEMENUHAN KONTRAK GAS - Prasetyoadi Susilo, Dwinanda
Reservoir X is a dry gas reservoir, situated in Y Field, which has been produced for seven years. It has been produced through three development wells; however, due to well integrity problem, there is only two wells left that can be produced as of now. In this study, a gas contract will be made using two production of said two wells, pointing to the remaining reserves. Material balance P/Z method will be used to determine Initial Gas In Place (IGIP) with production and pressure data from the development wells. Production optimization of the two wells will be conducted by choosing producing well which gives the best development scenario. Integrated modelling of the reservoir system, wells, and pipe network using MBAL, GAP and PROSPER software from Petroleum Experts is conducted for this study.